Dietary inflammatory index and risk of oesophageal cancer in Xinjiang Uyghur Autonomous Region, China - Tang, L.; Shivappa, N.; Hebert, J.; Lee, A.; Xu, F.; Binns, Colin (Cambridge University Press, 2018)
Diet has been shown to have an effect on both inflammation and oesophageal cancer. This study investigated the association between the dietary inflammatory index (DII ® ) and the risk of oesophageal cancer in Xinjiang Uyghur Autonomous Region, China. A case–control study was conducted during 2008–2009 in Urumqi and Shihezi. DII scores were calculated based on dietary intake assessed by a validated FFQ administered to 359 incident oesophageal cancer patients and 380 hospital-based controls. Higher DII scores indicate more pro-inflammatory diets. Logistic regression analyses were performed to assess the association between DII scores and oesophageal cancer risk. Oesophageal cancer patients had a significantly higher median DII score (-0·35; interquartile range (IQR)=-2·25, 1·86) than that of controls (-1·41; IQR -3·07, 0·40). Multivariable logistic analysis revealed a positive association between higher DII scores and oesophageal cancer risk (OR Quartile 4 v. 1 2·55; 95 % CI 1·61, 4·06; P trend < 0·001). A pro-inflammatory diet appears to be associated with an increased risk of oesophageal cancer in Xinjiang Uyghur Autonomous Region. Specific carcinogenic mechanisms are discussed. Accumulating evidence, to which the study contributes, indicates that encouraging the intake of more anti-inflammatory foods may be a strategy to protect against oesophageal cancer in this high-risk area of China.